An insight to Islamic philosophy and the Islamisation of philosophy - Moris, Megawati (AHAS KIRKHS, Department of Communication, IIUM, 2024)
Philosophy in the Islamic intellectual tradition is referred to both as falsafah and ḥikmah. The former term is the Arabisation of the Greek term philosophia meaning “love of wisdom” and the latter is the term taken from the Qur’ān to signify a Divine gift of abundant good, and wisdom derived from al-kitāb (the Book) and the prophets. Yet Muslims treat philosophy with suspicion and caution even when the Qur’ānic term hikmah (wisdom) refers to it.